(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract This article explores the challenges and effective strategies for delivering English for Specific Purposes (ESP) courses in multilingual classrooms. It highlights the complexities educators face while addressing language barriers that can impede learning in diverse student populations. By advocating for differentiated instruction, the use of visual aids, collaborative learning approaches, contextualized activities, constructive feedback, and cultural awareness, the article underscores how these strategies can create an inclusive and effective educational environment.